Evaluation of Material Characteristics of Fuel Tank Material Utilized For Agricultural Applications with Biofuels. (2018) - Prasad, Durga; Reddy, Akash R; Balan, A.S.S.; Joel, J.; Thangaraja, J.
Abstract: Numerous research works has been carried out to study the performance, combustion and emission characteristics of biofuels. Though these results are promising, the material compatibility of biofuels needs to be evaluated for durability and long term applications. Corrosion characteristics of biofuels are important for durability of fuel tanks and engine parts. Biofuels are hygroscopic, capable of absorbing moisture from the ambient and corrode the material to which it is exposed. The fuel wetted parts in a fuel supply system includes fuel pump, filter, injection pump and fuel tank. Caustic embrittlement of tank material is identified as the major cause with biodiesel fuels. Hence the current study is focused to access the corrosion behavior of biofuels in the conventional fuel tanks employed for agricultural applications. Static immersion test is conducted on mild steel specimen for a period of 720 hours and the corrosion rate was evaluated. The corrosion results observed for the test condition is negligible. However, ethanol has shown the highest corrosion rate in comparison with other samples.